PENGARUH PENERAPAN AKUNTANSI SEKTOR PUBLIK DAN PENGAWASAN INTERNAL TERHADAP KUALITAS LAPORAN REALISASI PELAKSANAAN APB DESA BALASARI KEC. POLEANG BARAT T.A 2023 - Sri Surti Ramadani; Sasmita Nabilah Syahrir; Surianto Ilham (Komunitas Manajemen Kompetitif, 2026)
The Effect of the Implementation of Public Sector Accounting and Internal Supervision on the Quality of the Realization Report of the Village Revenue and Expenditure Budget (APBDes) in Balasari Village, Poleang Barat District, Fiscal Year 2023. This research was conducted under the supervision of Sasmita Nabila Syahrir, SE., M.Ak., CA., ACPA as the first supervisor and Surianto Ilham, SE., M.Acc., Ak., CA as the second supervisor. The objective of this study is to understand the impact of public sector accounting implementation and internal supervision on the quality of the APBDes realization report. This study employs a quantitative method combined with an associative approach. Data collection was conducted using a questionnaire distributed to 45 respondents consisting of village officials and community members using purposive sampling. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results show that the implementation of public sector accounting does not have a significant effect on the quality of the APBDes realization report (p-value 0.226 > 0.05). Meanwhile, internal supervision has a positive and significant effect (p-value 0.000 < 0.05). This indicates that better internal supervision leads to better quality financial reports. On the other hand, the implementation of public sector accounting is not yet optimal due to limited competence of village officials and lack of training. This study concludes that improving the quality of village financial reports is more influenced by effective internal supervision. Therefore, the village government should strengthen supervision and provide training to improve transparency, accountability, and compliance with regulations